2019
DOI: 10.1002/sat.1301
|View full text |Cite
|
Sign up to set email alerts
|

Google QUIC performance over a public SATCOM access

Abstract: Google QUIC accounts for almost 10 % of the Internet traffic and the protocol is not standardized at the IETF yet. We distinguish Google QUIC (GQUIC) and IETF QUIC (IQUIC) since there may be differences between the two. Both Google and IETF versions run over UDP and cannot be split the way satellite systems usually do with TCP connections. The need for adapting any-QUIC parameters needs to be evaluated. Since GQUIC is available, we analyze its behavior over a satellite communication system. In our evaluations,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…What does exist is largely inconclusive. Some preliminary assessments have found that QUIC facilitates a 100% increase in satellite broadband page load times compared to PEP-accelerated TCP [42]. However, others suggest that QUIC performs better, measuring up to a 50% decrease page load times [43].…”
Section: A Qpep Design Objectivesmentioning
confidence: 99%
“…What does exist is largely inconclusive. Some preliminary assessments have found that QUIC facilitates a 100% increase in satellite broadband page load times compared to PEP-accelerated TCP [42]. However, others suggest that QUIC performs better, measuring up to a 50% decrease page load times [43].…”
Section: A Qpep Design Objectivesmentioning
confidence: 99%
“…With encrypted transport layer headers, as it is the case for VPNs and QUIC [4], PEPs can not be applied anymore. This leads to significant performance degradation described in earlier publications [5], [6], [2], [7], [8], [9], [10] and this work. Research, like [11], [12], that neglects the fact that PEPs are usually used to accelerate TCP connections, conclude that QUIC outperforms TCP on these satellite links.…”
Section: Introductionmentioning
confidence: 60%
“…Unfortunately, this becomes problematic in scenarios where proxies are used to enable connection splitting, as in wireless networks (we discuss this in more detail in Section I-B). In these settings, QUIC's performance diminishes versus connections carried over TCP and secured with TLS [9], [10]. Thus, while QUIC brings several benefits to remote networks, its encryption policies offset those advantages.…”
Section: A Recent Online Technology Trendsmentioning
confidence: 99%